Análisis de la gestión de compras públicas en la Dirección Distrital de Educación de Pichincha. - Chicaiza Chicaiza, Jimena Alexandra (2023)
The objective of this research work is to analyze the management of public purchases and its relationship with budget execution in the Pichincha District Education Department. Currently the District Office of Pichincha does not execute the total budget assigned to public purchases, there are several drawbacks in the related processes that derive from the different requesting units, since there are no guides for each district that stipulate the steps to follow in order to Execute an adequate and timely public procurement process. The applied methodology is of a descriptive type under the field modality based on the qualitative-quantitative approach with a deductive method.